Max Ernst - Gimferrer, Pere, 1945-; Petrová, Eva, 1928-2012 (Odeon, 1993)
Monografie věnovaná inspiračním zdrojům a životnímu osudu něm. malíře.
Životopisná data
Keywords: Ernst, Max, -- 1891-1976; malíři -- Německo -- 19.-20. století; německé malířství -- 19.-20. století; monografie